2018
DOI: 10.4236/ajps.2018.94067
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic and Productivity Performance for Quinoa Genotypes in an Agroecological and Conventional Production System

Abstract: The objective of this research was to evaluate the agronomic performance and productivity of sixteen genotypes of Chenopodium quinoa cultivated in agroecological and conventional production systems. The evaluations were carried out, based on agronomic characteristics and yields of sixteen C. quinoa genotypes, grown in two simultaneous experiments, in an agroecological production and a conventional production system carried out at the town of Entre Rios do Oeste, Paraná, Brazil in the harvest 2015/16. Each expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Days taken to 50 per cent blooming and for maturity of quinoa were found non-significant to different inter row spacings. This was similar to findings of Belmonte et al (2018) and Rishi and Galwey (1991). Interaction effect for above traits was found non-significant in quinoa with respect to different sowing windows and varied spacings.…”
Section: Rgr = (Log W − Log W ) (T − T )supporting
confidence: 92%
“…Days taken to 50 per cent blooming and for maturity of quinoa were found non-significant to different inter row spacings. This was similar to findings of Belmonte et al (2018) and Rishi and Galwey (1991). Interaction effect for above traits was found non-significant in quinoa with respect to different sowing windows and varied spacings.…”
Section: Rgr = (Log W − Log W ) (T − T )supporting
confidence: 92%
“…2005 (80-126 days) and Tan and Temel, 2018 (119-141 days) among the genotypes studied. Belmonte et al (2018) observed days to flowering ranging from 53.8 to 57.7 among the varieties investigated. It is reported that the physiological maturity of quinoa can be achieved within 70-90 days after flowering [49,50].…”
Section: Days To Maturitymentioning
confidence: 89%